ANALISIS PENGARUH PENDIDIKAN, PELATIHAN, DAN PENGEMBANGAN SDM TERHADAP KINERJA PEGAWAI - Kusufa, Fendiyatmi; Hidayat, Imam (Unitri Press, 2023)
This research aims to find out how the influence of education, training, and HR development on employee performance, while the type of data used in this study is a type of quantitative research, using primary data and data collection techniques through questionnaires distributed to employees of the Batang-Batang Sumenep sub-district where the results of the questionnaire were analyzed using SPSS version 26. The results of this study indicate that the dominant variables of education, training, and development have a significant effect on employee performance.